Should we try to manage non-financial interests?. (12th April 2018) - Wiersma, Miriam; Kerridge, Ian; Lipworth, Wendy; Rodwin, Marc
Abstract : Ideological biases influence medical research and practice and should be disclosed and managed, say Miriam Wiersma and colleagues . But Marc Rodwin argues that many of these interests are widespread and inherent to life and cannot be avoided or eliminated